A 10-week FIFA 11+ program improves the short-sprint and modified agility T-test performance in elite seven-a-side soccer players - Foqha, Batool Mohammed; Schwesig, René; Ltifi, Mohamed Amine; Bartels, Thomas; Hermassi, Souhail; Aouadi, Ridha (Frontiers in Physiology, 2023)
Objective: The primary objective of this study was to assess the effects of 10 weeks of FIFA 11+ training on the physical performance of elite seven-a-side soccer players. Methods: Twenty-five seven-a-side soccer players were recruited from two senior national teams. The players completed the following protocols during 10 weeks of training: a) FIFA 11+: The FIFA group (n = 13) underwent the FIFA 11+ program combined with regular soccer training; b) Dynamic conventional warm-up: The control group (n = 12) underwent regular soccer training. Their ability was validated using a pre-test followed by a post-test to measure the sprint performance (5-, 10-, and 20-m sprints), a modified agility T-test (MAT), and a five-jump test (FJT). Results: A comparison of pre- and post-tests for physical performance in each group demonstrated that the FIFA 11+ warm-up significantly improved the 10-m sprinting performance (p = 0.034; F = 5.04; ηp2 = 0.17) and reduced the time spent to perform the MAT (p = 0.000; F = 23.16; ηp2 = 0.52) in the FIFA group compared with the control group; however, no significant changes were observed in the 5- and 20-m sprints and FJT. Conclusion: The main findings of this research showed that the 10-week FIFA 11+ program led to significant improvements in the 10-m sprint and MAT compared to regular training among elite seven-a-side soccer players. Given these positive outcomes, further studies on the practical implementation and optimization of the FIFA 11+ program are warranted to provide valuable guidance for coaches and athletes, seeking to maximize its benefits in real-world settings.